Place of Grass and Legume in Soil Conservation - Rege, N D (Journal of Soil and Water Conservation, 2022)
This paper outlines the effect of physico- chemical changes, brought about by different frequencies of cultivation, on the yield of wheat. The data relatc to an investigation carried out during the season of 1951-52. It was observed that the percentage of water stable aggregates was higher under 9 ploughings as compared to 3, 6 and 12 ploughings. This increase may be explained on the basis of increased clay content of these aggregates. Since structure determines the water-air relationship of the soil, it was not unexpected to find that optimum moisture was present under 9 ploughings as compared to others. holding capacity also increased under 9 ploughings due, perhaps, to greater proportion of clay in the water stable aggregates. The percentage of carbon, as expected, was maximum under 3 ploughings and progressively decreased with the increase in the number of cultivations. The reason for this may be found in the increased micro- bial activities as stimulated by better aira- tion, consequently resulting in the quicker burning of carbon. The increase in nitrate nitrogen beyond 3 ploughings may be ex- plained in the same way. Similarly increase in the available phosphate under 9 ploughings may be due to it. For the reasons explained above, it may be logical to expect the highest yield under 9 ploughings which was 997•12, 260•64, .34•36 lb. more than 3, 6 and 12 ploughings res- pectively, though the differences between 9 and 12 ploughings were not statistically significant.